Grazing enhances belowground carbon allocation, microbial biomass, and soil carbon in a subtropical grassland - Chris H. Wilson; Michael S. Strickland; Jack A. Hutchings; Thomas S. Bianchi; S. Luke Flory (Global Change Biology, 2018)
Despite the large contribution of rangeland and pasture to global soil organic carbon ( SOC ) stocks, there is considerable uncertainty about the impact of large herbivore grazing on SOC , especially for understudied subtropical grazing lands. It is well known that root system inputs are the source of most grassland SOC , but the impact of grazing on partitioning of carbon allocation to root tissue production compared to fine root exudation is unclear. Given that different forms of root C have differing implications for SOC synthesis and decomposition, this represents a significant gap in knowledge. Root exudates should contribute to SOC primarily after microbial assimilation, and thus promote microbial contributions to SOC based on stabilization of microbial necromass, whereas root litter deposition contributes directly as plant‐derived SOC following microbial decomposition. Here, we used in situ isotope pulse‐chase methodology paired with plant and soil sampling to link plant carbon allocation patterns with SOC pools in replicated long‐term grazing exclosures in subtropical pasture in Florida, USA . We quantified allocation of carbon to root tissue and measured root exudation across grazed and ungrazed plots and quantified lignin phenols to assess the relative contribution of microbial vs. plant products to total SOC . We found that grazing exclusion was associated with dramatically less overall belowground allocation, with lower root biomass, fine root exudates, and microbial biomass. Concurrently, grazed pasture contained greater total SOC , and a larger fraction of SOC that originated from plant tissue deposition, suggesting that higher root litter deposition under grazing promotes greater SOC . We conclude that grazing effects on SOC depend on root system biomass, a pattern that may generalize to other C4‐dominated grasslands, especially in the subtropics. Improved understanding of ecological factors underlying root system biomass may be the key to forecasting SOC and optimizing grazing management to enhance SOC accumulation.